High Sensitivity Refractive Index Sensor Based on Multicoating Photonic Crystal Fiber With Surface Plasmon Resonance at Near-Infrared Wavelength - Duanming Li; Wei Zhang; Huan Liu; Jiangfei Hu; Guiyao Zhou (IEEE Photonics Journal, 2017)
A pure silica core photonic crystal fiber with multicoating layers for high refractive index (RI) sensing is proposed. Au is used as the active plasmonic material. Tantalum pentoxide is deposited on Au in order to prevent the oxidation and further enhance the evanescent field. The simulation was preformed through the full-vector finite element method (FEM), and the results show that the proposed fiber sensor can obtain the average wavelength sensitivity of 9180 nm/RIU with the analyte RI range of 1.40-1.44, corresponding to the resolution of 1.09 × 10-5 RIU. Moreover, the maximum amplitude sensitivity of 1739.26 RIU-1 with resolution of 5.75 × 10-6 RIU are also obtained. The designed sensor can be a potential candidate for microfluidic analyte detecting.